Examining the Effects of Different Exertion Levels and Reference Standards on the Diagnostic Accuracy of Exercise ECG for Detecting Coronary Artery Disease — A Pilot Study - Julius Heimann; Thomas Schramm; Martin Grauduszus; Christine Joisten (Annals of Noninvasive Electrocardiology)
ABSTRACT Background Exercise electrocardiogram (ECG) is frequently used for evaluating patients with suspected coronary artery disease (CAD). However, it has been downgraded in international guidelines due to a limited sensitivity and specificity, compared with other non‐invasive tests. Methods We hypothesized, that a sufficient exertion going beyond 85% of the age predicted maximal heart rate (APMHR), by considering the achieved level of workload can improve sensitivity and specificity of the exercise ECG. Secondly, the performance of exercise ECG, when evaluated against a functional reference standard has barely been investigated, although an improved diagnostic accuracy has been reported for other non‐invasive tests in this case. Therefore, in this pilot study, a total of 147 patients without known CAD who underwent exercise ECG followed by coronary angiography within 90 days were retrospectively evaluated. Results The combined end point of 85% of APMHR and 75% of the predicted workload showed a slight but not statistically significant benefit over APMHR alone (66.7% vs. 58.1%; p = 0.545). The sensitivity of ST‐segment depression was 51.3% for detecting anatomically defined CAD and 62.5% for functionally relevant CAD (p = 0.378). Conclusions Although the results of this pilot study lack statistical significance, the numeric differences clearly justify further research on this topic.